Indonesian Arabic Teachers Must Be Solutive In The Era Of Society 5.0 - Sa’adah, Hadiatus; Nurhadi, Nurhadi; Hilmi, Danial; Ni’mah, Lailatun (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2022)
The emergence of technological sophistication that they are proud of has resulted in the problem of decreasing attitudes and behavior experienced by millennial students. Attitudes caused include a lack of morals, cyberbullying, and gadget addiction. So, changes in behavior must be followed up by Arabic teachers, and the challenge for Arabic teachers in Indonesia is to meet the Era of Society 5.0. This study aims to show that Arabic language teachers and community components must be able to deal with complexities. And teachers must be able to build good and conducive communication with students, parents, and the community. The right step to deal with it is to think and act on a solution because it is part of creative thinking reform. Literature study is one approach in this research. Arabic teachers who think relatively must prepare themselves to face the challenges of society 5.0 using (1) always being optimistic, (2) having a solid work team, (3) being communicative teachers, (4) being hard workers, (5) commitment, (6) simplifying problems, not taking lightly. The author hopes that Arabic language teachers, communities, and stakeholders in Indonesia can together create students with innovative and solutive characters. <w:LsdException Locked="false" Priority="39" SemiHidden="true" Unh